Telemedicine for delivery of health care in Parkinson's disease. - Samii A; Ryan-Dykes P; Tsukuda RA; Zink C; Franks R; Nichol WP (Journal of Telemedicine & Telecare, 2006)
We have used telemedicine at the Seattle Veterans Administration Medical Center to deliver follow-up care to patients with Parkinson's disease (PD). Patients were located at eight facilities which were 67-2400 km from the medical centre. Each facility had videoconferencing equipment (connected by Internet Protocol at 384 kbit/s), and computer terminals that could access the patient's electronic medical record. Over a three-year period, we used telemedicine for 100 follow-up visits on 34 PD patients. Visits lasted 30-60 min. Patients and providers were satisfied with the use of the technology. Savings amounted to approximately 1500 attendant travel hours, 100,000 travel kilometres, and US 37,000 dollars in travel and lodging costs. For the first 82 telemedicine visits, the video quality was inadequate for scoring all components of the motor Unified Parkinson Disease Rating Scale (UPDRS). For the last 18 visits, a different videoconferencing unit produced better video quality, which was satisfactory for motor UPDRS measurements, except for components that required physical contact with the patient (rigidity and retropulsion testing). Our experience shows that telemedicine can be used effectively for follow-up visits with selected PD patients who are unable to travel.